Legal Protection and Certainty Management of Gold Mining in The Customary Rights of The Customary Law Community of Buru Regency, Maluku Province - Mukadar, Rustam (Jurnal Ilmiah Hukum dan Keadilan, 2026)
The rights of indigenous law communities over natural resources, particularly minerals and coal, are regulated under Article 33 paragraph (3) in conjunction with Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, as well as Law Number 3 of 2020 on Mineral and Coal Mining. Legal certainty in the utilization of mining resources has been concretely implemented at the Gunung Botak Gold Mining area in Buru Regency, which has been operating since 2011. This study employs a normative-empirical legal research method with an approach that examines the implementation of positive law in factual conditions within society. The findings indicate that Law Number 3 of 2020 does not specifically regulate the legal status of indigenous communities, despite the Constitutional Court Decision Number 35/PUU-X/2012, which provides legal protection and recognition of indigenous peoples’ rights to manage their natural resources. To achieve legal certainty in the utilization of gold mining at Gunung Botak, the Provincial Government of Maluku and the Buru Regency Government have proposed the designation of Mining Business License Areas (WIUP) and People’s Mining Areas (WPR), with People’s Mining Licenses managed in the form of cooperatives administered directly by the indigenous law community of Petuanan Kayeli, Buru Regency.